2010
DOI: 10.1111/j.1745-4573.2010.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Apple Polyphenol on Oxidative Stability of Sliced Cooked Cured Beef and Pork Hams During Chilled Storage

Abstract: The effects of apple polyphenol (AP) on color, lipid and protein oxidation in sliced cooked cured hams (SCCHs) made of pork and beef during chilled storage were investigated. SCCH samples with no antioxidant added and those treated with vitamin C were used as controls. The results indicated that addition of 500 ppm AP to the samples significantly inhibited discoloration in pork SCCH, but not in beef; all the AP treatments (with 300, 500 and 1,000 ppm AP) successfully inhibited lipid oxidation of both pork and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 33 publications
4
13
0
Order By: Relevance
“…However, total carbonyl values were significantly reduced (p<0.05) on days4 and 7 of storage in breast and thigh additive-treated samples compared with the control samples (Table2), except for breast meat treated with OE at 100 ppm, which presented an intermediate value. eRBCA-2019-0719 In general, these results are in agreement with those of Al-Hijazeen et al (2016a and b), and other researchers (Estevez et al, 2005;Sun et al, 2010), who reported that the total carbonyl values reached up to 5 nmol/mg protein in cooked chicken meat. The addition of BHA or E-300significantly reduced carbonyl values both in breast and thigh meats (p< 0.05) relative to the control treatment measured on day 7; however, among the tested additives, E-300 resulted in numerically higher total carbonyl values in thigh meat on day 7.…”
Section: Protein Oxidationsupporting
confidence: 90%
“…However, total carbonyl values were significantly reduced (p<0.05) on days4 and 7 of storage in breast and thigh additive-treated samples compared with the control samples (Table2), except for breast meat treated with OE at 100 ppm, which presented an intermediate value. eRBCA-2019-0719 In general, these results are in agreement with those of Al-Hijazeen et al (2016a and b), and other researchers (Estevez et al, 2005;Sun et al, 2010), who reported that the total carbonyl values reached up to 5 nmol/mg protein in cooked chicken meat. The addition of BHA or E-300significantly reduced carbonyl values both in breast and thigh meats (p< 0.05) relative to the control treatment measured on day 7; however, among the tested additives, E-300 resulted in numerically higher total carbonyl values in thigh meat on day 7.…”
Section: Protein Oxidationsupporting
confidence: 90%
“…This was in agreement with Xiao et al (2011) who also reported low total carbonyl value (0.46 to 0.81 nmol/mg protein) using raw ground chicken meat. The total carbonyl values were reported in the range of 2-5 nmol/mg protein using various cooked meat products (Requena et al, 2003;Sun et al, 2010;Estévez, 2011;Al-Hijazeen et al, 2016a, b). However, E-250 showed the lowest total carbonyl values at day 7 compared to the other treatments using the raw meat samples.…”
Section: Protein Oxidationmentioning
confidence: 99%
“…Furthermore, total carbonyl values in cooked meat were much higher than those of raw meat and reached up to 4 nmol/mg protein by the end of storage time (Table 4). Total estimated carbonyl values were reported in the range of 1-3 nmol/mg protein for raw meat and up to 5 nmol/mg protein for cooked meat (Estevez et al, 2005;Sun et al, 2010;Estevez, 2011). This increasing trend of total carbonyl formation was connected to the TBARS or MDA changing the rate of the SD treatment.…”
Section: Tablementioning
confidence: 92%